If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = -6 + 2x Reorder the terms: 3 + 4x = -6 + 2x Solving 3 + 4x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 4x + -2x = -6 + 2x + -2x Combine like terms: 4x + -2x = 2x 3 + 2x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 2x = -6 + 0 3 + 2x = -6 Add '-3' to each side of the equation. 3 + -3 + 2x = -6 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -6 + -3 2x = -6 + -3 Combine like terms: -6 + -3 = -9 2x = -9 Divide each side by '2'. x = -4.5 Simplifying x = -4.5
| 6x-(3-2x)=4-3(8-x) | | 8-3x-6=6.5 | | x+2x+64=148 | | 6.5(n-1)=-4 | | 125=5t^2+30t | | 35t=36 | | 2x-1/x=3 | | 7x+4y=68 | | 3-147=0 | | 45=5t^2+30t | | 5[x-(4x-5)]=7-8x | | x25/21 | | y--1=(2/3)(x-4) | | 5x^2-10=50 | | 1.08(2t+2.50)+3=t | | (2x+5w)(7x-w)= | | Y+5=-3(x-7) | | 14/7*8/7 | | 10-3x4x-5/-3 | | (x/9)=(x/10)-3 | | 10/5*6/8 | | a=11+b | | 2a^2+2ab+a^2+b^2+2ab-b^2=3a^2+4ab | | 2a^2+ab+a^2+b^2+2ab-b^2=3a^2+4ab | | 2x(2x-3)/5=20 | | 2a^2+a^2=3a^2 | | 1/18*2/3 | | x(6x-2)=(6x+8)(x-2) | | 2a*(a-b)=a^2-3ab | | 50-3m=8 | | 9+6n=4n+9 | | =4(x-5y)-5(2y-3x)-(2x-5y) |